PENGARUH PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI INDONESIA - Nugrahanto, Arif; Andri Nasution, Soupani (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
Several studies related to the effect of audits on taxpayer compliance provide different conclusions. Bergman and Nevarez (2006) find the fact that tax audits negatively affect compliance. In contrast, Gemmel and Ratto (2012) concluded that the audit had a negative effect on the group of taxpayers who obeyed, and at the same time had a positive effect on the group of taxpayers who did not comply. Given the different conclusions, the researcher is interested in testing in the Indonesian context by using the SIDJP data from the Directorate General of Tax for the period 2009-2013.The difference-in-differences approach model implemented in this study adopts Norman Gemmell and Marissa Ratto (2012). The dependent variable is income tax while the independent variable is the dummy variable for group, time and type of audits. Regression results show that the interaction coefficient between the dummy group variable and the time dummy variable which is the difference-in-differences coefficient, has a p-value that is statistically insignificant to reject null hypothesis. It tells that there is no difference in the level of compliance between the audited (corporate) taxpayer and non-audited (corporate) taxpayers. No impact on the level of compliance of taxpayers may come from several reasons, including the small coverage of the tax audits, the existence of the bomb crater effect, and the results of the type of updating audit risk.